Les misérables (2012) [videorecording (Blu-Ray)] - Jackman, Hugh; Crowe, Russell, 1964-; Hathaway, Anne, 1982-; Seyfried, Amanda; Redmayne, Eddie, 1982-; Tveit, Aaron; Bonham Carter, Helena, 1966-; Baron Cohen, Sacha, 1971-; Hugo, Victor, 1802-1885; Schönberg, Claude-Michel (Universal Pictures Home Entertainment, 2019)
In early 19th century France the paroled prisoner Jean Valjean seeks redemption, regains his social standing, and rises to the rank of mayor. He encounters a beautiful but desperately ill woman named Fantine and cares for her daughter, Cosette, after her death. All the while he is obsessively pursued by the policeman Javert, who vows to make him pay for the crimes of his past.